Preparation-method-dependent morphological, band structural, microstructural, and photocatalytic properties of noble metal-GaNbO4 nanocomposites - Devi, Suman; Kelkar, Sarika A.; Kashid, Vikas; Salunke, Hemant G.; Gupta, Narendra M. (RSC Advances, 2013)
We report the distinct physicochemical and photophysical properties of gallium niobate photocatalysts (bandgap: similar to 3.1 eV), prepared by a solid-state (SS) reaction and sol-gel (SG) method and dispersed with a noble metal (similar to 0.5% of Pt, Au, or RuOx) cocatalyst. SG-GaNbO4 comprised smaller size particles (similar to 20-50 nm) and a larger surface area (similar to 160 m(2) g(-1)) compared to SS-GaNbO4 (particle size similar to 30-150 nm, surface area similar to 27 m(2) g(-1)). XRD patterns revealed a preparation-dependent variation in the relative intensity of prominent reflections. In TEM examination, SG samples exhibited small-range grain boundaries and heterogeneous metal/substrate interfacial contacts, while SS-GaNbO4 had long-range ordering. Laser-Raman and thermoluminescence investigations revealed that lattice distortion, defect-induced inter-bandgap charge trapping states, and the local environment around the metal/semiconductor interfaces may also depend on the preparation method. Metal-GaNbO4 nanocomposites showed no activity for the dissociation of pure water under UV (>250 nm) irradiation, despite the favourable conduction and valence band potentials. This was attributed to the sharp Ga and Nb d-levels in the narrow conduction band of GaNbO4, as confirmed by ab initio electronic structure calculation. These photocatalysts, however, showed good activity for semiconductor-mediated photo-dissociation of aqueous methanol to produce H-2; a cocatalyst-dependent activity trend, Pt > RuOx > Au, was observed. Doping of S at similar to 5% of the oxygen sites led to decreased photoactivity, ascribed to the presence of localized S 3p states just above the O 2p valence level. In conclusion, besides band characteristics, certain morphological and microstructural properties play a crucial role in the photoactivity of the metal/oxide nanocomposites.

Photophysical, bandstructural, and textural properties of o-FeNbO4 in relation to its cocatalyst-assisted photoactivity for water oxidation - Babu, Robin; Kelkar, Sarika A.; Kashid, Vikas; Achary, Srungarpu N.; Salunke, Hemant G.; Gupta, Narendra M. (RSC Advances, 2014)
In this study, a relationship between physicochemical, photophysical and photocatalytic properties of hydrothermally synthesized orthorhombic iron niobate (FeNbO4) is investigated. o-FeNbO4 displayed a multi-regime optical absorbance, which was ascribed to at least two distinct phenomena: (i) bandgap (similar to 3.4 eV) excitation giving rise to UV absorbance and (ii) energy transitions involving disorder-induced sub-bandgap donor or acceptor states leading to visible light absorbance. The preparation-dependent distortion in the crystal lattice and the existence of closely spaced inter-bandgap energy states were corroborated by powder X-ray diffraction, photoluminescence, thermoluminescence, and Raman spectroscopy studies. The first principles electronic structure elucidation and photoelectrochemical measurements supported a wide bandgap for FeNbO4, in contrast to the narrow bandgap reported previously. Correspondingly, a small photocurrent density was observed for FeNbO4 (similar to 2 to 3 mu A cm(-2)) under 1 sun illumination, suggesting the availability of a smaller cross section of photogenerated charge pairs. Following these band characteristics, while no H-2 evolution was observed, FeNbO4 gave rise to particle size-dependent O-2 evolution during visible light irradiation of water in the presence of electron scavengers, the samples loaded with NiO as cocatalyst showing better activity. Further, the transmission electron microscopy examination revealed the dominant exposure of (011) facets of FeNbO4, besides a significant heterogeneity of inter-domain boundaries. Overall, our results confirm that the photoactivity of metal/oxide nanocomposites is governed by a combination of factors, such as: grain morphology, microstructure, surface adsorption states, and the localized inter-bandgap energy states. Our study also reveals that, in contrast to prevalent assumptions, the wavelength at the absorption edge may not represent the true band-to-band energy gap of metal oxide semiconductors, which is relevant to their photocatalytic activity.

Low frequency noise and photo-enhanced field emission from ultrathin PbBi2Se4 nanosheets - Suryawanshi, Sachin R.; Guin, Satya N.; Chatterjee, Arindom; Kashid, Vikas; More, Mahendra A.; Late, Dattatray J.; Biswas, Kanishka (Journal of Materials Chemistry C, 2016)
Atomically thin two-dimensional layered materials have gained wide interest owing to their novel properties and potential for applications in nanoelectronic and optoelectronic devices. Here, we present the spectral analysis and photo-enhanced field emission studies of a layered intergrowth PbBi2Se4 nanosheet emitter, performed at the base pressure of similar to 1 x 10(-8) mbar. The emitter shows a turn-on field value of similar to 4.80 V mu m(-1), corresponding to an emission current density of similar to 1 mu A cm(-2). Interestingly, when the cathode was illuminated with visible light, it exhibited a lower turn-on field of B3.90 V mm(-1), and a maximum emission current density of similar to 893 mu A cm(-2) has been drawn at an applied electric field of similar to 8.40 V mu m(-1). Furthermore, the photo-enhanced emission current showed reproducible, step-like switching behavior in synchronous with ON-OFF switching of the illumination source. The emission current-time plots reveal excellent stability over a duration of similar to 6 h. Low-frequency noise is a significant limitation for the performance of nanoscale electronic devices. The spectral analysis performed on a Fast Fourier Transform (FFT) analyzer revealed that the observed noise is of 1/f(alpha) type, with the value of alpha similar to 0.99. The low frequency noise, photo-enhanced field emission, and reproducible switching behavior characterized with very fast rise and fall times propose the layered PbBi2Se4 nanosheet emitter as a new promising candidate for novel vacuum nano-optoelectronic devices.